Gut microbiota and metabolites in patients with COVID-19 are altered by the type of SARS-CoV-2 variant - Yokoyama, Yoshihiro; Ichiki, Tomoko; Yamakawa, Tsukasa; Tsuji, Yoshihisa; Kuronuma, Koji; Takahashi, Satoshi; Narimatsu, Eichi; Katanuma, Akio; Nakase, Hiroshi (Frontiers in Microbiology, 2024)
Patients with COVID-19 have dysbiosis of the intestinal microbiota with altered metabolites in the stool. However, it remains unclear whether the differences among SARS-CoV-2 variants lead to differences in intestinal microbiota and metabolites. Thus, we compared the microbiome and metabolome changes for each SARS-CoV-2 variant in patients with COVID-19.We conducted a multicenter observational study of patients with COVID-19 and performed fecal microbiome, metabolome, and calprotectin analyses and compared the results among the different SARS-CoV-2 variants.Twenty-one patients with COVID-19 were enrolled and stratified according to the SARS-CoV-2 strain: six with the Alpha, 10 with the Delta, and five with the Omicron variant. Fecal microbiome analysis showed that α-diversity was reduced in the order of the Omicron, Delta, and Alpha variants (P=0.07). Linear discriminant analysis revealed differences in the abundance of short-chain fatty acid-producing gut microbiota for each SARS-CoV-2 variant. Fecal metabolome analysis showed that the Omicron and Delta variants had markedly reduced propionic and lactic acid levels compared to the Alpha strain (P < 0.05).The intestinal microbiota of patients with COVID-19 varies depending on the SARS-CoV-2 variant.Dysbiosis of the intestinal microbiota due to differences in SARS-CoV-2 variants causes a decrease in intestinal short-chain fatty acids.